PENGARUH KOMPENSASI DAN DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN DI HOTEL ASANA AGUNG PUTRA BALI - Asa Dana, Ni Made Sashia; Dewi, A.A. Sagung Kartika (E-Jurnal Manajemen, 2016)
Bali is one destination tourism destination in Indonesia, and therefore a lot of tourists and foreign tourists who built the hotel in Bali especially Kuta area. The performance of good employees is necessary for improving guests' satisfaction and improve the company. The purpose of this study was to determine the effect of compensation and organizational support on employee performance at Hotel Asana Agung Putra Bali. The population used in this study were 45 employees. The data collection was done by interview, observation and questionnaires. Data analysis technique used is multiple linear regression analysis and using the F test and t test. The research results show that the compensation effect on employee performance Asana Agung Putra Hotel Bali and the support of influential organizations on employee performance Asana Agung Putra Hotel Bali. The implication of this is that companies should provide incentives and bonuses in accordance with the role or position of the employee and the employee must be given training.
Keywords: compensation; organizational support; employee performance